The Development and Initial Validation of a Health Belief Model Scale to Reduce Single Cigarette Use among Urban, African American Smokers. Issue 5 (2nd September 2020) - Phan, Lilianna; Beck, Kenneth; Wang, Min Qi; Butler, James
ABSTRACT: Background: Single cigarette use among urban African Americans can perpetuate smoking continuation. There are no measures on perceptions related to reducing single cigarette use. Purpose: We developed the Beliefs and Self-Efficacy for Singles (BASES) Scale to measure beliefs related to reducing this behavior. Methods: We used a multiphase approach including qualitative interviews with 25 users, consultation with 3 experts, and pilot testing with 24 users. The scale items were administered to 122 users to examine psychometric properties including reliability and validity. Exploratory factor analysis via principal axis factoring with oblique rotation was conducted. Results: BASES is a 20-item scale to predict perceived benefits, barriers, susceptibility, severity, and self-efficacy related to reducing single cigarette use. BASES' internal consistency was α = 0.87 and subscale consistencies were αs = 0.71– 0.85. BASES demonstrated moderate convergent validity ( r = 0.43, p <.001) and strong discriminant validity ( r = 0.01, p >.05). Discussion: Each subscale measures a dimension of intrapersonal beliefs that may support reducing single cigarette use. Translation to Health Education Practice: BASES provides health educators and cessation practitioners with a measure of malleable beliefs including perceived benefits, susceptibility, and self-efficacy related to reducing single cigarette use to inform health education design.